2020
DOI: 10.1109/jsen.2020.3022376
|View full text |Cite
|
Sign up to set email alerts
|

American Sign Language Recognition Using RF Sensing

Abstract: Many technologies for human-computer interaction have been designed for hearing individuals and depend upon vocalized speech, precluding users of American Sign Language (ASL) in the Deaf community from benefiting from these advancements. While great strides have been made in ASL recognition with video or wearable gloves, the use of video in homes has raised privacy concerns, while wearable gloves severely restrict movement and infringe on daily life. Methods: This paper proposes the use of RF sensors for HCI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Note that high-pass filtering for ground clutter removal was only applied on the 25 GHz FMCW and 7-10 GHz UWB sensors, and not the 77 GHz FMCW sensor. Due to the finer detail offered the higher millimeter wave transmit frequency, we have found that many deep neural networks (DNNs) actually perform better when the ground clutter not filtered out [25]. This is because the filtering operation removes not just the clutter, but also low-frequency signal components, which may be of interest in gesture recognition and other finescale problems, such as incurred in assisted living applications.…”
Section: Indoor Human Activity Classification Datasetmentioning
confidence: 99%
“…Note that high-pass filtering for ground clutter removal was only applied on the 25 GHz FMCW and 7-10 GHz UWB sensors, and not the 77 GHz FMCW sensor. Due to the finer detail offered the higher millimeter wave transmit frequency, we have found that many deep neural networks (DNNs) actually perform better when the ground clutter not filtered out [25]. This is because the filtering operation removes not just the clutter, but also low-frequency signal components, which may be of interest in gesture recognition and other finescale problems, such as incurred in assisted living applications.…”
Section: Indoor Human Activity Classification Datasetmentioning
confidence: 99%
“…Compilation of large datasets for training state-of-the-art deep neural networks is difficult when human subjects are involved, not only because of the time involved in measuring numerous iterations of each class, but also because it can be difficult to recruit participants, especially if from a minority population, such as the Deaf community. In previous work [7], 20 native ASL signs were classified with an accuracy of 72.5% using minimum-redundancy maximum-relevance (mRMR) selection of 150 handcrafted features extracted from a five node multi-frequency RF sensor network and a random forest classifier. To surpass this performance with just a single sensor, recent advances in deep learning, which have yielded great advances in related fields [15], can be applied.…”
Section: Word-level Asl Recognitionmentioning
confidence: 99%
“…Unfortunately, this approach is not effective because imitation signing does have kinematic flaws that render them distinguishable from native ASL signing. This is evidenced not only by their differentiability using a support vector machine classifier [7], but also by the poor classification approach attained when deep learning is applied. When a convolutional neural network (CNN) is pre-trained on imitation data and fine tuned with 80% of the native ASL-R dataset, only 46.15% accuracy was attained when testing on the remaining 20% of native ASL-R data.…”
Section: Word-level Asl Recognitionmentioning
confidence: 99%
See 2 more Smart Citations